Вы находитесь на странице: 1из 10

Types of Pendulums - differential equations and

solutions
Simple Pendulum

Let’s consider a massless light rod of length, l, carrying a load of mass, m. The
pendulum is oscillating due to an angular displacement of 

The torque about the pivot point P is given by

𝑇𝑜𝑟𝑞𝑢𝑒, 𝜏𝑝 = −𝑚𝑔𝑙 𝑠𝑖𝑛𝜃 … … … (1.1)

The moment of inertia of a point mass about the pivot point P is given by

𝐼𝑝 = 𝑚𝑙 2

The rotational equation of motion is given by

𝜏𝑝 = 𝐼𝑝 𝛼 … … … (1.2)

𝑑2 𝜃
Where 𝛼 is the angular acceleration, 𝛼 = .
𝑑𝑡 2

From (1.1) and (1.2) we get,

𝐼𝑝 𝛼 = −𝑚𝑔𝑙 𝑠𝑖𝑛𝜃

𝑑2𝜃
𝑚𝑙 2 = −𝑚𝑔𝑙 𝑠𝑖𝑛𝜃
𝑑𝑡 2

𝑑2 𝜃 𝑔
2
= − 𝑠𝑖𝑛𝜃
𝑑𝑡 𝑙

The above equation is the nonlinear harmonic oscillator equation. To


linearize the problem, the angular deflection, , is considered to be too small such
that 𝑠𝑖𝑛𝜃 = 𝜃. In that case, our equation of motion reduces to
𝑑2𝜃 𝑔
2
= − 𝜃
𝑑𝑡 𝑙

The above equation is the simple harmonic oscillator equation.

Solution
𝑔
If 𝜃0 is the initial angular displacement (Amplitude) and 𝜔 = √ 𝑙 is the
angular velocity of the pendulum bob, then the solution to the simple harmonic
oscillator equation is as follows

𝑔
𝜆2 + =0
𝑙

𝑔
𝜆 = ±√ 𝑖
𝑙

The roots are complex. So the equations should be of the form

𝜃(𝑡) = 𝑒 𝛼𝑡 (𝐴1 cos(𝑏𝑡) + 𝐴2 sin(𝑏𝑡))

𝑔
𝛼 = 0, 𝑏 = √
𝑙

𝑔 𝑔
∴ 𝜃(𝑡) = (𝐴1 cos (√ 𝑡) + 𝐴2 sin (√ 𝑡))
𝑙 𝑙

To determine constants 𝐴1 and 𝐴2 , we need to use boundary conditions

𝜃(0) = 𝜃0 , 𝜃′(0) = 0

Substituting in the equation for 𝜃(𝑡), we get

𝐴1 = 𝜃0 , 𝐴2 = 0

𝑨𝒏𝒈𝒖𝒍𝒂𝒓 𝑫𝒊𝒔𝒑𝒍𝒂𝒄𝒆𝒎𝒆𝒏𝒕, 𝜽(𝒕) = 𝜽𝟎 𝐜𝐨𝐬(𝝎𝒕)

𝒅𝜽(𝒕)
𝑨𝒏𝒈𝒖𝒍𝒂𝒓 𝑽𝒆𝒍𝒐𝒄𝒊𝒕𝒚, = 𝝎(𝒕) = −𝝎𝜽𝟎 𝐬𝐢𝐧(𝝎𝒕)
𝒅𝒕
Physical Pendulum

A physical pendulum consists of a rigid body that undergoes rotation in a


fixed axis about a fixed pivot point S. 𝑙𝑐𝑚 denote the distance of the center of mass
from the pivot point S. The torque analysis of a physical pendulum is similar to that
of a simple pendulum. The torque about the pivot point S is given by

𝑇𝑜𝑟𝑞𝑢𝑒, 𝜏𝑝 = −𝑚𝑔𝑙𝑐𝑚 𝑠𝑖𝑛𝜃 … … … (2.1)

The moment of inertia of the pendulum about the pivot point S is given by
2
𝐼𝑆 = 𝑚𝑙𝑐𝑚 + 𝐼𝑐𝑚

Where 𝐼𝑐𝑚 is the moment of inertia of the body about the center of mass.

The rotational equation of motion is given by

𝜏𝑝 = 𝐼𝑆 𝛼 … … … (2.2)

𝑑2 𝜃
Where 𝛼 is the angular acceleration, 𝛼 = .
𝑑𝑡 2

From (2.1) and (2.2) we get,

𝐼𝑆 𝛼 = −𝑚𝑔𝑙𝑐𝑚 𝑠𝑖𝑛𝜃

2
𝑑2𝜃
(𝑚𝑙𝑐𝑚 + 𝐼𝑐𝑚 ) = −𝑚𝑔𝑙𝑐𝑚 𝑠𝑖𝑛𝜃
𝑑𝑡 2

𝑑2𝜃 𝑚𝑔𝑙𝑐𝑚
= − 𝑠𝑖𝑛𝜃
𝑑𝑡 2 2 +𝐼 )
(𝑚𝑙𝑐𝑚 𝑐𝑚

The above equation is the nonlinear differential equation of a Physical


pendulum. To linearize the problem, the angular deflection, , is considered to be
too small such that 𝑠𝑖𝑛𝜃 = 𝜃 (Similar to the previous case). In that case, our
equation of motion reduces to
𝑑2𝜃 𝑚𝑔𝑙𝑐𝑚
= − 𝜃
𝑑𝑡 2 2 +𝐼 )
(𝑚𝑙𝑐𝑚 𝑐𝑚

The above equation is the simple harmonic oscillator equation of a physical


Pendulum.

Solution
𝑚𝑔𝑙𝑐𝑚
If 𝜃0 is the initial angular displacement (Amplitude) and 𝜔 = √(𝑚𝑙2 is
𝑐𝑚 +𝐼𝑐𝑚 )

the angular velocity of the physical pendulum, then the solution to the simple
harmonic oscillator equation is as follows

𝑚𝑔𝑙𝑐𝑚
𝜆2 + 2 +𝐼 )
=0
(𝑚𝑙𝑐𝑚 𝑐𝑚

𝑚𝑔𝑙𝑐𝑚
𝜆 = ±√ 2 +𝐼 )
𝑖
(𝑚𝑙𝑐𝑚 𝑐𝑚

The roots are complex. So the equations should be of the form

𝜃(𝑡) = 𝑒 𝛼𝑡 (𝐴1 cos(𝑏𝑡) + 𝐴2 sin(𝑏𝑡))

𝑚𝑔𝑙𝑐𝑚
𝛼 = 0, 𝑏 = √ 2 +𝐼 )
(𝑚𝑙𝑐𝑚 𝑐𝑚

𝑚𝑔𝑙𝑐𝑚 𝑚𝑔𝑙𝑐𝑚
∴ 𝜃(𝑡) = (𝐴1 cos (√ 2
𝑡) + 𝐴2 sin (√ 2 +𝐼 )
𝑡))
(𝑚𝑙𝑐𝑚 + 𝐼𝑐𝑚 ) (𝑚𝑙𝑐𝑚 𝑐𝑚

To determine constants 𝐴1 and 𝐴2 , we need to use boundary conditions

𝜃(0) = 𝜃0 , 𝜃′(0) = 0

Substituting in the equation for 𝜃(𝑡), we get

𝐴1 = 𝜃0 , 𝐴2 = 0

𝑨𝒏𝒈𝒖𝒍𝒂𝒓 𝑫𝒊𝒔𝒑𝒍𝒂𝒄𝒆𝒎𝒆𝒏𝒕, 𝜽(𝒕) = 𝜽𝟎 𝐜𝐨𝐬(𝝎𝒕)

𝒅𝜽(𝒕)
𝑨𝒏𝒈𝒖𝒍𝒂𝒓 𝑽𝒆𝒍𝒐𝒄𝒊𝒕𝒚, = 𝝎(𝒕) = −𝝎𝜽𝟎 𝐬𝐢𝐧(𝝎𝒕)
𝒅𝒕
Torsional Pendulum

Let’s consider a thin, massless light rod carrying a disk with a moment of
inertia about the center of mass 𝐼𝑐𝑚 and the disk rotates in a horizontal plane.

When the disk is rotated away from it’s equilibrium position by an angle then the
rod exerts a restoring torque about the center of mass of the disk and is given by

𝜏𝑐𝑚 = −𝑘𝜃 … … … (3.1)

Where k is the torsional constant. It is a characteristic property of the rod.

The rotational equation of motion is given by

𝜏𝑐𝑚 = 𝐼𝑐𝑚 𝛼 … … … (3.2)

𝑑2 𝜃
Where 𝛼 is the angular acceleration, 𝛼 = .
𝑑𝑡 2

From (3.1) and (3.2) we get,

𝐼𝑐𝑚 𝛼 = −𝑘𝜃

𝑑2𝜃
𝐼𝑐𝑚 2 = −𝑘𝜃
𝑑𝑡

𝑑2𝜃 𝑘
2
= − 𝜃
𝑑𝑡 𝐼𝑐𝑚

The above equation is the simple harmonic oscillator equation.

Solution
𝑘
If 𝜃0 is the initial angular displacement (Amplitude) and 𝜔 = √𝐼 is the
𝑐𝑚

angular velocity of the disk, then the solution to the simple harmonic oscillator
equation is as follows
𝑘
𝜆2 + =0
𝐼𝑐𝑚

𝑘
𝜆 = ±√ 𝑖
𝐼𝑐𝑚

The roots are complex. So the equations should be of the form

𝜃(𝑡) = 𝑒 𝛼𝑡 (𝐴1 cos(𝑏𝑡) + 𝐴2 sin(𝑏𝑡))

𝑘
𝛼 = 0, 𝑏 = √
𝐼𝑐𝑚

𝑘 𝑘
∴ 𝜃(𝑡) = (𝐴1 cos (√ 𝑡) + 𝐴2 sin (√ 𝑡))
𝐼𝑐𝑚 𝐼𝑐𝑚

To determine constants 𝐴1 and 𝐴2 , we need to use boundary conditions

𝜃(0) = 𝜃0 , 𝜃′(0) = 0

Substituting in the equation for 𝜃(𝑡), we get

𝐴1 = 𝜃0 , 𝐴2 = 0

𝑨𝒏𝒈𝒖𝒍𝒂𝒓 𝑫𝒊𝒔𝒑𝒍𝒂𝒄𝒆𝒎𝒆𝒏𝒕, 𝜽(𝒕) = 𝜽𝟎 𝐜𝐨𝐬(𝝎𝒕)

𝒅𝜽(𝒕)
𝑨𝒏𝒈𝒖𝒍𝒂𝒓 𝑽𝒆𝒍𝒐𝒄𝒊𝒕𝒚, = 𝝎(𝒕) = −𝝎𝜽𝟎 𝐬𝐢𝐧(𝝎𝒕)
𝒅𝒕
Compound Pendulum

A compound pendulum consists of a disk of radius R and mass 𝑚𝑑 fixed at


the end of a rigid rod of mass 𝑚𝑟 and length l, which undergoes rotation in a fixed
axis about a fixed pivot point. The torque analysis of a compound pendulum is
similar to that of a physical pendulum. The torque about the pivot point is given by

𝑇𝑜𝑟𝑞𝑢𝑒, 𝜏 = −(𝑚𝑟 𝑙𝑐𝑚 + 𝑚𝑑 𝑙)𝑔 𝑠𝑖𝑛𝜃

The center of mass of the rod from the pivot is given by

𝑙𝑐𝑚 = 𝑙/2

So the torque equation becomes

𝑇𝑜𝑟𝑞𝑢𝑒, 𝜏 = −(𝑚𝑟 (𝑙/2) + 𝑚𝑑 𝑙)𝑔 𝑠𝑖𝑛𝜃 … … … (4.1)

The moment of inertia of the pendulum about the pivot point S is given by

𝐼 = 𝐼𝑟𝑜𝑑 + 𝐼𝑑𝑖𝑠𝑘
1
Where 𝐼𝑟𝑜𝑑 = 3 𝑚𝑟 𝑙 2 is the moment of inertia of the rod about the pivot and
𝐼𝑑𝑖𝑠𝑘 = 𝑚𝑑 𝑙 2 + 𝐼𝑐𝑚,𝑑𝑖𝑠𝑘 is the moment of inertia of the disk about the pivot.
1
𝐼𝑐𝑚,𝑑𝑖𝑠𝑘 = 2 𝑚𝑑 𝑅 2 is the moment of inertia about the center of mass. So,
1
𝐼𝑑𝑖𝑠𝑘 = 𝑚𝑑 𝑙 2 + 2 𝑚𝑑 𝑅 2 .

1 1
𝐼 = 𝑚𝑟 𝑙 2 + 𝑚𝑑 𝑙 2 + 𝑚𝑑 𝑅 2
3 2

The rotational equation of motion is given by

𝜏𝑝 = 𝐼𝛼 … … … (4.2)
𝑑2 𝜃
Where 𝛼 is the angular acceleration, 𝛼 = .
𝑑𝑡 2

From (1.1) and (1.2) we get,

1
𝐼𝛼 = − ( 𝑚𝑟 𝑙 + 𝑚𝑑 𝑙) 𝑔 𝑠𝑖𝑛𝜃
2

1 2 2
1 2
𝑑2𝜃 1
( 𝑚𝑟 𝑙 + 𝑚𝑑 𝑙 + 𝑚𝑑 𝑅 ) 2 = − ( 𝑚𝑟 𝑙 + 𝑚𝑑 𝑙) 𝑔 𝑠𝑖𝑛𝜃
3 2 𝑑𝑡 2

1
𝑑2𝜃 (2 𝑚𝑟 + 𝑚𝑑 ) 𝑔𝑙
= − 𝑠𝑖𝑛𝜃
𝑑𝑡 2 1 1
(3 𝑚𝑟 𝑙 2 + 𝑚𝑑 𝑙 2 + 2 𝑚𝑑 𝑅 2 )

The above equation is the nonlinear differential equation of a compound


pendulum. To linearize the problem, the angular deflection, , is considered to be
too small such that 𝑠𝑖𝑛𝜃 = 𝜃 (Similar to the previous cases). In that case, our
equation of motion reduces to

1
𝑑2𝜃 (2 𝑚𝑟 + 𝑚𝑑 ) 𝑔𝑙
= − 𝜃
𝑑𝑡 2 1 2 2 1 2
(3 𝑚 𝑟 𝑙 + 𝑚 𝑑 𝑙 + 2 𝑚 𝑑 𝑅 )

The above equation is the simple harmonic oscillator equation of a compound


Pendulum.

Solution
If 𝜃0 is the initial angular displacement (Amplitude) and 𝜔 =
1
( 𝑚𝑟 +𝑚𝑑 )𝑔𝑙
1
2
1 is the angular velocity of the Compound pendulum, then the
( 𝑚𝑟 𝑙2 +𝑚𝑑 𝑙2 + 𝑚𝑑 𝑅 2 )
3 2
solution to the simple harmonic oscillator equation is as follows

1
(2 𝑚𝑟 + 𝑚𝑑 ) 𝑔𝑙
𝜆2 + =0
1 1
(3 𝑚𝑟 𝑙 2 + 𝑚𝑑 𝑙 2 + 2 𝑚𝑑 𝑅 2 )

1
( 𝑚𝑟 + 𝑚𝑑 ) 𝑔𝑙
𝜆 = ±√ 2 𝑖
1 1
(3 𝑚𝑟 𝑙 2 + 𝑚𝑑 𝑙 2 + 2 𝑚𝑑 𝑅 2 )
The roots are complex. So the equations should be of the form

𝜃(𝑡) = 𝑒 𝛼𝑡 (𝐴1 cos(𝑏𝑡) + 𝐴2 sin(𝑏𝑡))

1
(2 𝑚𝑟 + 𝑚𝑑 ) 𝑔𝑙
𝛼 = 0, 𝑏 = √
1 1
(3 𝑚 𝑟 𝑙 2 + 𝑚 𝑑 𝑙 2 + 2 𝑚 𝑑 𝑅 2 )

1
(2 𝑚𝑟 + 𝑚𝑑 ) 𝑔𝑙
∴ 𝜃(𝑡) = 𝐴1 cos (√ 𝑡)
1 1
(3 𝑚𝑟 𝑙 2 + 𝑚𝑑 𝑙 2 + 2 𝑚𝑑 𝑅 2 )
(
1
(2 𝑚𝑟 + 𝑚𝑑 ) 𝑔𝑙
+ 𝐴2 sin (√ 𝑡)
1 1
(3 𝑚𝑟 𝑙 2 + 𝑚𝑑 𝑙 2 + 2 𝑚𝑑 𝑅 2 )
)

To determine constants 𝐴1 and 𝐴2 , we need to use boundary conditions

𝜃(0) = 𝜃0 , 𝜃′(0) = 0

Substituting in the equation for 𝜃(𝑡), we get

𝐴1 = 𝜃0 , 𝐴2 = 0

𝑨𝒏𝒈𝒖𝒍𝒂𝒓 𝑫𝒊𝒔𝒑𝒍𝒂𝒄𝒆𝒎𝒆𝒏𝒕, 𝜽(𝒕) = 𝜽𝟎 𝐜𝐨𝐬(𝝎𝒕)

𝒅𝜽(𝒕)
𝑨𝒏𝒈𝒖𝒍𝒂𝒓 𝑽𝒆𝒍𝒐𝒄𝒊𝒕𝒚, = 𝝎(𝒕) = −𝝎𝜽𝟎 𝐬𝐢𝐧(𝝎𝒕)
𝒅𝒕
Type of Pendulum Differential Equation Solutions

𝑑2𝜃 𝑔 𝑔
Simple = − 𝜃 𝜃(𝑡) = 𝜃0 cos (√ 𝑡)
𝑑𝑡 2 𝑙 𝑙
𝑔 𝑔
𝜔(𝑡) = −√ 𝜃0 sin (√ 𝑡)
𝑙 𝑙
𝑑2𝜃 𝑚𝑔𝑙𝑐𝑚
= − 𝑠𝑖𝑛𝜃 𝑚𝑔𝑙𝑐𝑚
Physical 𝑑𝑡 2 (𝑚𝑙𝑐𝑚
2 +𝐼 )
𝑐𝑚 𝜃(𝑡) = 𝜃0 cos (√ 𝑡)
(𝑚𝑙𝑐𝑚
2 +𝐼 )
𝑐𝑚

𝑚𝑔𝑙𝑐𝑚 𝑚𝑔𝑙𝑐𝑚
𝜔(𝑡) = −√ 2 +𝐼 ) 0
𝜃 sin (√ 𝑡)
(𝑚𝑙𝑐𝑚 𝑐𝑚 (𝑚𝑙𝑐𝑚
2 +𝐼 )
𝑐𝑚

Torsional 𝑑2𝜃 𝑘
= − 𝜃 𝑘
𝑑𝑡 2 𝐼𝑐𝑚 𝜃(𝑡) = 𝜃0 cos (√ 𝑡)
𝐼𝑐𝑚

𝑘 𝑘
𝜔(𝑡) = −√ 𝜃0 sin (√ 𝑡)
𝐼𝑐𝑚 𝐼𝑐𝑚
1 1
𝑑2𝜃 (2 𝑚𝑟 + 𝑚𝑑 ) 𝑔𝑙 (2 𝑚𝑟 + 𝑚𝑑 ) 𝑔𝑙
Compound = − 𝜃
𝑑𝑡 2 1 1 𝜃(𝑡) = 𝜃0 cos (√ 𝑡)
( 3 𝑚𝑟 𝑙 2 + 𝑚𝑑 𝑙 2 + 2 𝑚𝑑 𝑅 2 ) 1 1
( 3 𝑚𝑟 𝑙 + 𝑚𝑑 𝑙 2 + 2 𝑚𝑑 𝑅 2 )
2

1 1
(2 𝑚𝑟 + 𝑚𝑑 ) 𝑔𝑙 (2 𝑚𝑟 + 𝑚𝑑 ) 𝑔𝑙
𝜔(𝑡) = −√ 𝜃0 sin (√ 𝑡)
1 2 2 1 2 1 1
( 3 𝑚𝑟 𝑙 + 𝑚𝑑 𝑙 + 2 𝑚𝑑 𝑅 ) ( 3 𝑚 𝑟 𝑙 + 𝑚𝑑 𝑙 2 + 2 𝑚𝑑 𝑅 2 )
2